2008
DOI: 10.4141/cjss07005
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic and heterotrophic respiration rates across a chronosequence of hybrid poplar plantationsin northern Alberta

Abstract: . 2008. Autotrophic and heterotrophic respiration rates across a chronosequence of hybrid poplar plantations in northern Alberta. Can. J. Soil Sci. 88: 261Á272. Distinction of autotrophic (root, R r ) versus heterotrophic (R h ) soil respiration is important to understanding C balance in forest ecosystems and the contribution of both respiration components to total soil respiration (R s ) may change as stands mature. We studied R r and R h in a chronosequence of hybrid poplar plantations that were 4, 6, 8, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
1
14
1
Order By: Relevance
“…Saurette et al . (, ) reported F c rates, ranging from 1 to 5 μmol m −2 s −1 for 3‐ to 11‐year‐old hybrid poplar plantations. In a 15‐year‐old hybrid poplar plantation, intercropped with agricultural crops, Peichl et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saurette et al . (, ) reported F c rates, ranging from 1 to 5 μmol m −2 s −1 for 3‐ to 11‐year‐old hybrid poplar plantations. In a 15‐year‐old hybrid poplar plantation, intercropped with agricultural crops, Peichl et al .…”
Section: Discussionmentioning
confidence: 99%
“…and Acer spp. (Cisneros‐Dozal et al ., ), 60% for beech stand ( Fagus sylvatica ) (Epron et al ., ), 56% for Pinus sylvestris L. (Högberg et al ., ), 47% (Saurette et al ., ), and 65–85% for a hybrid poplar (Arevalo et al ., ). These studies, however, measured root respiration during the growing season only.…”
Section: Discussionmentioning
confidence: 99%
“…Saurette et al (2008) reported that there was no significant difference of R h between plantations at different growth ages. However, the significant difference of R h was found in this study (p<0.05), the R h was highest in the middle-age plantation and then followed by the mature plantation.…”
Section: Effects Of Stands At Different Ages On R Hmentioning
confidence: 95%
“…Most of the previous studies about R h focus on the inland forest ecosystems (Hanson et al 2000;Ngao et al 2007;Saurette et al 2008;Gaumont-Guay et al 2008), and very few concerns coastal forest (Tyree et al 2006). As so far, no available information has been found on R h in coastal forest ecosystem in China.…”
Section: Introductionmentioning
confidence: 94%
“…NEP also depends on stand age (i.e., different amplitudes in R e ), and given the mature and old forest sites examined in this study, our findings may not be applicable to young forests and other ecosystems (e.g., crops, grasslands). Because the components of soil respiration differ among forests of various ages [42,43], caution should be used when applying our results to young forests. Therefore, further analysis and evaluation would facilitate extension of our results to more ecosystems in diverse ecoregions.…”
Section: Discussionmentioning
confidence: 99%